PENINGKATAN AKTIVITAS DAN PRESTASI BELAJARMELALUI PENDEKATAN SAINTIFIK PADA MATA PELAJARAN IPA MATERI ALAT INDRA DAN PEMELIHARAANYA KELAS IV SD N 2 KALIBENING KABUPATEN WONOSOBO TAHUN AJARAN 2017/2018 - Herman Herman; Panji Hidayat (Universitas Ahmad Dahlan, 2018)
The process of teaching and learning activities of science subjects The material of the Indra and Maintenance Equipment which is usually done is lecture and only emphasize on the book. Teaching activities centered on teachers. Learners prefer to listen and record rather than ask or express opinions. Passive state of learners make a mistake pahama concept of teaching materials. The scientific approach is expected to increase activity and learning achievement. This study is a classroom action research consisting of two cycles. Subjects in this study were students class IV SD N 2 Kalibening 2017/2018 academic year which amounted to 20 children. Data collection techniques include observation, tests, interviews, and field notes. Data analysis using quantitative and qualitative analysis. The success criteria of action are said to be active if the number of active learners reaches 61% -80%. Criteria for the success of science learning achievement The material of Indra and Pemelihraanya which escaped KKM is 75% â‰¥ 81%.The results showed that learning with scientific approach has increased. Improvement can be seen in terms of activity and learning achievement of learners. In cycle I the percentage of activity reached 50% and increased in cycle II to reach 74%. Percentage increase in cycle I is 55% and increase in cycle II by 90%. It is concluded that the application of scientific approach can improve the activity and learning achievement of the fourth grade students of SD N 2 Kalibening in the science learning of the material of the sensory equipment and its maintainers.